DINAMIKA KURIKULUM PENDIDIKAN AGAMA KRISTEN: SEBUAH KAJIAN KOMPREHENSIF TENTANG PERKEMBANGAN DAN IMPLEMENTASINYA - Mea, Firmina; Seme, Yosua Chris A (Inculco Journal of Christian Education, 2025)
Christian religious education in Indonesia faces challenges in aligning its curriculum with the changing needs of society. This study aims to explore the dynamics and implementation of the Christian religious education curriculum and its impact on student character formation. The method used is a literature study, which includes an analysis of literature related to curriculum development. The results of the study indicate that factors such as government policies and contributions from educational institutions influence the effectiveness of the curriculum. The implications of this study highlight the need for curriculum development that is more responsive and adaptive to pluralistic social and cultural contexts, as well as the need for collaboration between educational institutions and the church.